2014
DOI: 10.1155/2014/572805
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Myxoid Liposarcoma of the Retroperitoneum: A Challenging Tumour for Diagnosis and Treatment

Abstract: Retroperitoneal sarcomas are rare neoplasms that account for only 1%-2% of all solid tumors and liposarcomas represent the most frequent histological type. We describe the case of a 44-year-old female with a retroperitoneal myxoid liposarcoma of 22 × 19 × 8 cm in size. The only symptoms were persistent pain and progressive tenderness of the abdomen lasting for two months. The mass was radically excised during laparotomy. CT and MRI were useful to clarify the site of origin of the tumor, relationships with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
1
10
0
3
Order By: Relevance
“…Pervious cohort studies have demonstrated that DLPS has the highest risk for both local and distant recurrence, while WDLPS has the lowest risk. [19,31] In this cohort, however, no statistically signi cant difference exists in different subtypes (Table 4, 5). Nonetheless, recurrence and death rate was lowest in WDLPS subtype, and highest in DLPS subtype, which was in accordance with previous researches.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pervious cohort studies have demonstrated that DLPS has the highest risk for both local and distant recurrence, while WDLPS has the lowest risk. [19,31] In this cohort, however, no statistically signi cant difference exists in different subtypes (Table 4, 5). Nonetheless, recurrence and death rate was lowest in WDLPS subtype, and highest in DLPS subtype, which was in accordance with previous researches.…”
Section: Discussionsupporting
confidence: 89%
“…As a subtype of sarcoma, liposarcoma accounts for approximately 15% of all sarcomas, making it the most common soft tissue sarcoma. [5] LPS mostly occurs in extremities, followed by retroperitoneum, and there are also literatures reporting LPS founded in rare locations, such as mediastinum, larynx or paratesticular. [20][21][22] High occurrence of retroperitoneum may be attributed to metastasis of LPS from other parts of body, especially where fat is abundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical distribution of liposarcoma is related to the histologic type with well differentiated, myxoid/round-cell liposarcomas and pleomorphic variants having a striking predilection for the limbs,while dedifferentiated liposarcoma occurs predominantly in the retroperitoneum. The risk of distant metastasis and survival are influenced by histological type with well differentiated, myxoid variants with a better outcome than pleomorphic and round cell types [1], [2].…”
Section: Discussionmentioning
confidence: 99%
“…Liposarcoma comprises of 15% of adult sarcomas and predominantly affect the extremities [1]. About 10–20% of sarcomas arise from the retroperitonium and includes a heterogenous list of histological types [2]. The most common site for abdominal liposarcoma is the retroperitonium.…”
Section: Introductionmentioning
confidence: 99%